STRATEGI BAURAN PEMASARAN KERAJINAN TENUN IKAT PADA CV. SILVI MN PARADILA DI DESA PARENGAN KECAMATAN MADURAN KABUPATEN LAMONGAN - Nasehatul Khoiriyah; Joko Widodo; Hety Mustika Ani (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2017)
The marketing mix strategy is one of the efforts undertaken by the company to increase product sales and earn profits for the company consisting of four groups, namely: product, price, promotion, and place or distribution channel. This study aims to describe the marketing mix strategy related to product, price, promotion, and place conducted by the owner of tenun ikat handicraft business of CV. Silvi MN Paradila in Parengan village, Maduran district, Lamongan regency. This research is a descriptive qualitative research. Determination of research location uses purposive area method, while the determination of subject and informant research using purposive method. Data collection uses observation methods, interviews, and documents. Data analysis used in this research is data reduction, data presentation, and drawing conclusion. The result of the research shows that marketing mix strategy related to product, price, promotion, and place conducted by the owner of tenun ikat handicraft business, namely: product strategy by maintaining product quality, and providing various motives. Pricing strategies are by setting the selling price of the cost of goods and profit margins and setting prices based on 3 levels: low, medium, and high. Promotional strategies are with advertising, publicity, personal selling, and direct marketing. As for the distribution is using direct and indirect distribution.